Mining TCGA database for prognostic genes in head and neck squamous cell carcinoma microenvironment - Qiu-Chi Ran; Sheng-Rong Long; Yan Ye; Chen Xie; Zhuo-Lin XuXiao; Yu-Song Liu; Hong-Xia Pang; Diwas Sunchuri; Nai-Chia Teng; Zhu-Ling Guo (Journal of Dental Sciences, 2021)
Background/purpose: Head and neck squamous cell carcinoma (HNSCC) is one of the most common malignant tumors. The aim of this study was to elucidate the effect of tumor microenvironment-related genes on the prognosis of HNSCC and to obtain tumor microenvironment-related genes that can predict poor prognosis in HNSCC patients. Materials and methods: The ESTIMATE algorithm was applied to the HNSCC transcriptomic data downloaded from the TCGA (The cancer genome atlas), and then the samples were divided into two groups: high and low immune scoring groups, and high and low basal scoring groups to screen for differentially expressed genes (DEGs) associated with poor patient outcomes. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis was performed to explore the potential functions of DEGs, and then to explore the potential prognostic value of individual DEGs. The results of survival analysis between DEGs and overall survival (OS) to explore tumor microenvironment-related genes relevant to the prognosis of HNSCC patients. Results: Fifty-nine tumor microenvironment-related genes were screened for association of OS with HNSCC (P < 0.05). The GO and KEGG enrichment analysis showed that the selected DEGs may mediate immune response, extracellular matrix, and immunoglobulin binding via neutrophil activation in HNSCC. Six of these DEGs, GIMAP6, SELL, TIFAB, KCNA3, P2RY8 and CCR4 were most significantly associated with OS (P < 0.001). Conclusion: We identified six tumor microenvironment-related genes that were significantly associated with poor prognosis in HNSCC. These genes may inspire researchers to discover new targets and approaches for HNSCC treatment.